Structural and functional Studies of angucycline tailoring enzymes - Patrikainen, Pekka (fi=Turun yliopisto|en=University of Turku|, 2015)
Polyketides are a diverse group of natural products produced in many bacteria, fungi and plants. These metabolites have diverse biological activities and several members of this group are in clinical use as antibiotics, anticancer agents, antifungals and immunosuppressants. The different polyketides are produced by polyketide synthases, which catalyze the condensation of extender units into various polyketide scaffolds. After the biosynthesis of the polyketide backbone, more versatility is created to the molecule by tailoring enzymes catalyzing for instance hydroxylations, methylations and glycosylations. Flavoprotein monooxygenases (FPMO) and short-chain alcohol dehydrogenases/reductases (SDR) are two enzyme families that catalyze unusual tailoring reactions in the biosynthesis of natural products. In the experimental section, functions of homologous FPMO and SDR tailoring enzymes from five different angucycline pathways were studied in vitro. The results revealed how different angucyclinones are produced from a common intermediate and that FPMO JadH and SDR LanV are responsible for the divergence of jadomycins and landomycins, respectively, from other angucyclines. Structural studies of these tailoring enzymes revealed differences between homologous enzymes and enabled the use of structure-based protein engineering. Mutagenesis experiments gave important information about the enzymes behind the evolution of distinct angucycline metabolites. These experiments revealed a correlation between the substrate inhibition and bi-functionality in JadH homologue PgaE. In the case of LanV, analysis of mutagenesis results revealed that the difference between the stereospecificities of LanV and its homologues CabV and UrdMred is unexpectedly related to the conformation of the substrate rather than to the structure of the enzyme. Altogether, the results presented here have improved our knowledge about different steps of angucycline biosynthesis and the reaction mechanisms used by the tailoring enzymes behind these steps. This information can hopefully be used to modify these enzymes to produce novel metabolites, which have new biological targets or possess novel modes-of-action. The understanding of these unusual enzyme mechanisms is also interesting to enzymologists outside the field of natural product research.